Comparison of the physiological responses to different small-sided games in elite young soccer players - Köklü, Y.; Asci, A.; Kocak, F. Ü.; Alemdaroglu, U.; Dündar, U. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to compare the blood lactate (La-), heart rate (HR) and percentage of maximum HR (%HRmax) responses among the small-sided games (SSGs) in elite young soccer players. Sixteen players (average age 15.7 ± 0.4 years; height 176.8 ± 4.6 cm; body mass 65.5 ± 5.6 kg; Vo2max 53.1 ± 5.9 ml/kg/min; HRmax 195.9 ± 7.4 b/min) volunteered to perform the YoYo intermittent recovery test and 6 bouts of soccer drills including 1-a-side, 2-a-side, 3-a-side, and 4-a-side games without a goalkeeper in random order at 2-day intervals. The differences in La-, HR and %HRmax either among the SSGs or among the bouts were identified using 4 × 6 (games × exercise bouts) 2-way analysis of variance with repeated measures. Significant differences were found on La-, HR, and %HRmax among the bouts (p = 0.05). The 3-a-side and 4-a-side games were significantly higher than 1-a-side and 2-a-side games on HR and %HRmax (p = 0.05), whereas the 1-a-side game significantly resulted in higher La- responses compared to other SSGs. This study demonstrated that physiological responses during the 1-a-side and 2-a-side games were different compared to 3-a-side and 4-a-side games. Therefore, it can be concluded that a decreased number of players results in increased intensity during SSGs including 6 bouts. These results suggest that coaches should pay attention on choosing the SSG type and the number of bouts to improve desired physical conditioning of elite young soccer players in soccer training.